Effectiveness of curcumin Longa and Piper Betle extracts to disinfect diabetic bacteria. (2020) - Idris Chin, Idzuan; Karim, Sabrina
Abstract: The present study aims to extract curcumin from turmeric (Curcuma Longa) and hydroxychavicol from betel leaves (Piper Betle) using Soxhlet Extractor as well as to identify the composition of each compound through FTIR spectroscopy. Subsequently, to assess the activity of both active compounds with various diabetic bacteria; Escherichia coli, MRSA, Candida albicans, Proteus mirabilis, and Yersinia sp. through disc diffusion method. As time progresses, more and more synthetic drugs are produced and consumed due to its reliability and efficiency despite that they contain a certain amount of toxicity that may harm the human body. Traditional herbs (therapeutic plants) have been exploited and were proven effective even in contemporary studies on antimicrobial activities and can be as an alternative for future applications. With the Soxhlet method, highest extraction yields for both samples; Curcuma Longa and Piper Betle, were 41.52% and 34.93% respectively. FTIR spectrums of both turmeric and betel have shown the presence of a hydroxyl group which indicates the presence of interchangeable protons from alcohol at wavelengths of 3350.06 cm-1 and 3341.91 cm-1 respectively. It was convinced that this functional group acted against pathogenic bacteria because of the antioxidant properties. betel (Piper Betle) has shown better inhibitory activity than turmeric (Curcuma Longa) against MRSA, P. mirabilis, E. coli, and C. albicans. It was also observed that with curcumin, higher concentration (10%) gives out the best diameter values. Ultimately, betel (Piper Betle) has shown better inhibitory activity than turmeric (Curcuma Longa) against MRSA, P. mirabilis, E. coli, and C. albicans.